The essential works of Thomas More - More, Thomas, Saint, 1478-1535; Wegemer, Gerard, 1950-; Smith, Stephen W. (New Haven ; London : Yale University Press, 2020)
"The first comprehensive one-volume collection of St.Thomas More's writing In this book, Wegemer and Smith assemble More's most important English and Latin works for the first time in a single volume. This volume reveals the breadth of More's writing and includes a comprehensive selection of his works on theology, political philosophy, and law, as well as his poetry and prose. It provides the most complete picture of More's work available and will serve as a major, foundational resource for early modern scholars, teachers, and students."--Publisher.
Map of London -- List of illustrations -- General preface / Center for Thomas More Studies -- Abbreviations -- Chronology -- English poetry -- Lucian dialogues and declamations -- The life of John Pico -- The history of King Richard III -- Utopia -- Epigrams -- Letters : 1501 to March 1534 -- Letters : on humanism, 1505-20 -- The four last things -- A response to Luther (selections) -- A dialogue of Sir Thomas More, knight (Dialogue concerning heresies) -- The supplication of souls -- The confutation of Tyndale's answer (selections) -- The apology of Sir Thomas More, knight -- The debellation of Salem and Bizance (selections) -- The answer to a poisoned book -- A treatise upon the passion of Christ -- A treatise to receive the blessed body -- A dialogue of comfort -- The sadness of Christ -- Letters : prison years, 1534-1535 -- Instructions, meditations, and prayers -- Thomas More's trial reconstructed -- Earliest biographical accounts and collected editions -- Online resources -- Selective glossary.
In English; some works translated from the original Latin.
Online resource; title from digital title page (viewed on January 24, 2020).
JSTOR
Keywords: More, Thomas, -- Saint, -- 1478-1535.; More, Thomas, -- Saint, -- 1478-1535; PHILOSOPHY -- History & Surveys -- Renaissance